Kunst in Europa 1920-1960 : Een confrontatie - Internationale tentoonstelling. - Bafcop, Marc; Balthazar, Herman; Volkaert, Walter; van Daele, D. (Mechelen : Cultureel Centrum A. Spinoy, 1976)
Alechinsky, Pierre ; Appel, Karel ; Archipenko, Alexander ; Arp, Hans (Jean) ; Aubroeck, Karel ; Bacon, Francis ; Beckmann, Max ; van den Berghe, Frits ; De Boeck, Felix ; Bourdelle, Antoine ; Brancusi, Constantin ; Braque, Georges ; Brusselmans, Jean ; Burssens, Jan ; Campendonk, Heinrich ; Chadwick, Lynn ; Chagall, Marc ; De Chirico, Giorgio ; Closon, Herman-J. ; Cox, Jan ; D'Haese, Roel ; Delaunay, Robert ; Delaunay, Sonia ; Delvaux, Paul ; Dix, Otto ; Dodeigne, Eugène ; Domenech, Salvador Dali y ; Dubuffet, Jean ; Duchamp, Marcel ; Ensor, James ; Ernst, Max ; Francis, Sam ; Gentils, Vic ; Giacometti, Alberto ; Gris, Juan ; Grosz, George ; Hartung, Hans ; Hepworth, Barbara ; Herbin, Auguste ; Van Hoeydonck, Paul ; Jawlensky, Alexej von ; Jespers, Floris ; Jespers, Oscar ; Jorn, Asger ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kokoschka, Oskar ; Kollwitz, Kathe ; Landuyt, Octave ; Larinov, Mikhail ; Laurencin, Marie ; Laurens, Henri ; Leger, Fernand ; Lehmbruck, Wilhelm ; Lhote, André ; Lipchitz, Jacques ; Macke, August ; Magnelli, Alberto ; Magritte, René ; Malfait, Hubert ; Man Ray ; Manzu, Giacomo ; Mara, Pol ; Marc, Franz ; Marini, Marino ; Masereel, Frans ; Matisse, Henri ; Miotte, Jean ; Miro, Joan ; Modigliani, Amedeo ; Mondriaan, Piet ; Moore, Henry ; Munch, Edvard ; Nolde, Emil ; Peeters, Jozef ; Permeke, Constant ; Pevsner, Antoine ; Piaubert, Jean ; Picabia, Francis ; Picasso, Pablo ; Poliakoff, Serge ; Pollock, Jackson ; Raveel, Roger ; Rouault, Georges ; Schmidt-Rottluff, Karl ; Servaes, Albert ; Servranckx, Victor ; Severini, Gino ; Slabbinck, Rik ; De Smet, Gust ; Somville, Roger ; Spilliaert, Léon ; De Troyer, Prosper ; Van Tuerenhout, Jef ; Tytgat, Edgard ; Vasarely, Victor ; Wijnants, Ernest ; de Woestyne, Gustave Van ; etc.
2 delen
Kunst in Europa 1920-1960 : Een confrontatie - Internationale tentoonstelling, Cultureel Centrum A. Spinoy, Mechelen, 26 september - 28 november 1976
biografie
Nederlands
kunstcatalogus